Modeling volatility persistence and asymmetry with exogenous breaks in the Nigerian stock returns - David A. Kuhe (CBN Journal of Applied Statistics, 2018)
This study examines the volatility persistence and asymmetry with exogenous breaks in Nigerian stock market. The study utilizes daily closing quotations of stock prices from the Nigerian stock exchange for the period 3rd July, 1999 to 12th June, 2017. Standard symmetric GARCH (1,1), asymmetric EGARCH (1,1) and GJR-GARCH (1,1) models with and without structural breaks were employed to measure shocks persistence and leverage effects in the presence of varying distributional assumptions. The empirical findings showed high persistence of shocks in the return series for the estimated models. However, the study found significant reduction in shocks persistence when structural breaks were incorporated in the estimated models. Empirical evidence for the existence of asymmetry without leverage effect was found in Nigerian stock market. The EGARCH (1,1) model with student-t innovation density was found to fit the data better than other competing models. The study recommends the incorporation of structural breaks while estimating volatility in the Nigerian stock market. This will help to avoid over-estimation of volatility shocks and restore investor's confidence in the stock market.
Keywords: C22; C32; C52; 330; Asymmetry; GARCH Family Models; Leverage Effect; Nigeria; Shock Persistence; Volatility